Choix d’études et rapports à la mobilité des lycéens et étudiants martiniquais - Gilles Joseph; Éric Kamwa; Sébastien Mathouraparsad (Études Caribéennes)
This article presents the main results of a survey conducted among students from the Schœlcher Campus (University of the Antilles, Martinique) and students from the Lycée de Bellevue in Fort-de-France, on their main motivations to go to study out of Martinique and not to, possibly, consider their return once these ended. High school students and students from Martinique seem to be mostly dissatisfied with the diversity of the training offer whose attractiveness is considered average, while recognizing an attractive study environment. While students generally seem quite satisfied with their experience, high school students seem sceptical about the degree of recognition by employers of degrees offered in Martinique. Thus, although they do not predominantly have a bad image of higher education in Martinique, only one third of high school students interviewed say they want to continue their studies in Martinique after the Baccalaureate, while a little less than half wants to leave.